Promoting Sustainable Human Settlements and Eco-City Planning Approach: Southeastern Anatolia Region and Southeastern Anatolia Project (Gap) in Turkey as a Case Study - Acma, Bulent (UNISCI Discussion Papers, 2005)
Sin resumen